Poly[bis(phenethylammonium) [dibromidoplumbate(II)]-di-μ-bromido]] - Shibuya, Kengo (International Union of Crystallography, 2009)
Crystals of the title compound, {(C(6)H(5)C(2)H(4)NH(3))(2)[PbBr(4)]}(n), were grown at room temperature from a solution in N,N-dimethylformamide (DMF) using nitromethane as the poor solvent. This perovskite-type organic–inorganic hybrid compound consists of well ordered sheets of corner-sharing disordered PbBr(6) octahedra separated by bilayers of phenethylammonium cations. The octahedra are rotated and tilted due to N—H⋯Br hydrogen bonds with the ammonium groups, generating a superstructure in the unit cell similar to that of the tetrachloridoplumbate (C(6)H(5)C(2)H(4)NH(3))(2)[PbCl(4)].